Comparison of Intraocular Pressure Measurement by Goldmann Applanation Tonometer, Air Puff Tonometer and Tonopen in Vitrectomized Eyes - Ghani, Muhammad Usman; Mukhtar, Muhammad Ahsan; Khan, Taimoor Ashraf; Shahid, Muhammad; Rauf, Abdul; Taimoor, Ijlal (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare Goldmann applanation tonometer, air puff tonometer, and tonopen measured IOP Readings in vitrectomized eyes filled with temponading oils and gasses.Study Design: Comparative cross-sectional study.Place and Duration of Study: Armed Forces Institute of Ophthalmology (AFIO), Rawalpindi Pakistan, from Aug 2021 to Feb2022.Methodology: A total of 50 eyes were included in our study. Intraocular pressure was measured by an experienced ophthalmologist between 10am to 4pm on the 7th postoperative day by three devices, Goldmann applanation tonometer (GAT), air puff tonometer, and tonopen. Pearson’s correlation and paired samples t-test was applied to determine correlation and any significant difference between the mean of intraocular pressure measured by three different devices.Results: Out of the 50 people included in study 31(62%) were males and 19(38%) were females. The mean age of study participants was 50.10±11.61 years. Mean intraocular (IOP) pressure measured by the GAT applanation tonometer was 14.59±1.13 mmHg. Mean IOP as calculated by the airpuff tonometer was 15.93±1.88 mmHg, whereas mean IOP as calculated by tonopen was 15.85±1.86 mmHg. All three instrument values showed significant difference as p-value < 0.001.Conclusions: The air puff tonometer overestimates IOP as compared to GAT. Tonopen and air puff tonometer produce IOP measurements that are similar and consistent to each other but not to GAT